2017
DOI: 10.1111/scs.12513
|View full text |Cite
|
Sign up to set email alerts
|

Supporting patients in reducing postoperative constipation: fundamental nursing care – a quasi‐experimental study

Abstract: Patients with hip fractures that were actively involved in their own care in preventing constipation were significantly less constipated 30 days after surgery than control patients. Increases in fluid and fibre intakes had significant effects on reducing the risk of developing constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 45 publications
1
32
0
4
Order By: Relevance
“…Pedersen's interpretation of Larsen's and Green's models has so far been tested in three doctoral theses in 2010–2017 dealing with issues of fundamentals of care: Hørdam et al. in on mobilising patients, Larsen, Thomsen, and Pedersen in on patients’ self‐care when it comes to heart failure and Trads, Deutch, and Pedersen in on prevention of postoperative obstipation.…”
Section: Person‐oriented Care: An Epistemological Approachmentioning
confidence: 99%
“…Pedersen's interpretation of Larsen's and Green's models has so far been tested in three doctoral theses in 2010–2017 dealing with issues of fundamentals of care: Hørdam et al. in on mobilising patients, Larsen, Thomsen, and Pedersen in on patients’ self‐care when it comes to heart failure and Trads, Deutch, and Pedersen in on prevention of postoperative obstipation.…”
Section: Person‐oriented Care: An Epistemological Approachmentioning
confidence: 99%
“…Several healthcare professionals described the need to communicate with the patient about experiences of bowel function; however, it was healthcare professionals who decided which treatment options should be initiated. A person-centered approach where patient's needs and subjective experience are taken into account has demonstrated better patient outcomes (43). To enable this, it is required that a person-centered approach is founded in the institutional leadership (44).…”
Section: Discussionmentioning
confidence: 99%
“…A person-centered approach where patient's needs and subjective experience are taken into account has demonstrated better patient outcomes. 43 To enable this, it is required that a person-centered approach is founded in the institutional leadership. 44 Another key finding of the present study was the different strategies that the participants reported for treating constipation.…”
Section: Dovepressmentioning
confidence: 99%
“…43 To enable this, it is required that a person-centered approach is founded in the institutional leadership. 44 Another key finding of the present study was the different strategies that the participants reported for treating constipation. They described the importance of adhering to individual strategies as well as general strategies used on the ward, but they stated that pharmacological strategies were most commonly used and enabled individualized care.…”
Section: Dovepressmentioning
confidence: 99%